Use of interval data envelopment analysis, goal programming and dynamic eco-efficiency assessment for sustainable supplier management. (May 2019) - Torres-Ruiz, Aineth; Ravindran, A. Ravi
Highlights: Comprehensive method for the management of supplier sustainability performance. Data Envelopment Analyses (DEA) used to estimate supplier eco-efficiency. Dynamic monitoring of supplier eco-efficiency through a Malmquist approach. Bicriteria optimization model integrating order quantity discounts. Methodology demonstrated with real data from an auto parts manufacturer. Abstract: Two big challenges for sustainable supplier management consist of (1) properly integrating the multiple factors necessary to measure the sustainability performance of suppliers and (2) modeling the dynamic nature of those factors. In this study, we demonstrate the aggregation of environmental and economic supplier performance criteria into a single (eco-efficiency) index using Data Envelopment Analysis (DEA) for interval data. Suppliers are pre-qualified according to this index and are allocated orders using multiple criteria models for single and multiple sourcing. In multiple sourcing, preemptive, non-preemptive and fuzzy goal programming models are used with purchase price and eco-efficiency as conflicting objectives. Finally, eco-efficiency change is assessed using an approach based on the Malmquist productivity index, which monitors suppliers over time. Thus, our methodology can be used for supplier evaluation, selection and monitoring. Data obtained from an auto parts manufacturer is used to illustrate the proposed method.